2014
DOI: 10.1177/0890334414547274
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Exclusive Breastfeeding at Hospital Discharge in Rural Western Australia

Abstract: The findings suggest that hospital practices are strong predictors of exclusive breastfeeding. Greater emphasis on Baby-Friendly hospital practices in the early postpartum period may help the establishment of exclusive breastfeeding, assisting rural mothers to reach established international breastfeeding recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 42 publications
(91 reference statements)
1
27
0
3
Order By: Relevance
“…185 Finally, one Australian population cohort study (the Australian Longitudinal Study on Women's Health) assessed self-reported breastfeeding and postpartum depression for each birth (at ages 31 to 36 years). 196 Postpartum depression was ascertained with the question, "Were you diagnosed or treated for postnatal depression? "; breastfeeding was categorized as less than 6 months vs. more than 6 months or more for each child.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…185 Finally, one Australian population cohort study (the Australian Longitudinal Study on Women's Health) assessed self-reported breastfeeding and postpartum depression for each birth (at ages 31 to 36 years). 196 Postpartum depression was ascertained with the question, "Were you diagnosed or treated for postnatal depression? "; breastfeeding was categorized as less than 6 months vs. more than 6 months or more for each child.…”
Section: Resultsmentioning
confidence: 99%
“…Interpretation of this result is limited by lack of information on the temporal sequence of depression and breastfeeding cessation. 196 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 As with antenatal education groups, early parenting groups might provide opportunities for new parents to share experiences and gain support for issues including breastfeeding. Positive attitudes towards breastfeeding are highly influential on breastfeeding outcomes in rural settings.…”
Section: Discussionmentioning
confidence: 99%